KAJIAN ERGONOMI PADA FASILITAS DUDUK UNIVERSITAS KRISTEN PETRA SURABAYA - Mulyono, Grace (Dimensi Interior, 2010)
A sitting facility is an important element contributing to the effectiveness of teaching activities in a classroom. Using the quantitative and descriptive method of approach, this research takes the classroom in Petra Christian University as the research location. Main data, verbal data from informant, written dan visual documentations such as videos and photos are used as data sources. The factors to be researched from the four types of classroom chairs include aspects of dimension, material form and colour and their relevance to the user. This research aims to describe to what extent has ergonomic principles been applied to the classroom chairs in order to maintain the user’s comfort. The results of the evaluation of the four types of chair show that 77% of the Siwangi chairs could be used with comfort because they are in line with the user’s anthropometry. However, the other types of chair particularly the metal wood and Chettos chairs could only be used by 30% of the user population because the dimensions where not in line with the average user’s anthropometry.